Konservasi Keanekaragaman Hayati dalam Islam - Kamila, Himmatul Hurria (UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG, 2024)
Biodiversity is one of the components of the environment which plays an important role in shaping the ecosystem that provides life support on Earth. For that reason, the efforts to provide protection is necessary. Islam is very much aware of the important role of biodiversity, therefore Islam have participated in biodiversity conservation through Islamic thought. The conservation of biodiversity in Islamic thoughts is shown through various rules sourced from the Qur’an, hadith and fatwas of para. Indonesia as a country with the second largest biodiversity in the world and a country with the largest Muslim majority population in the world has an important role to play in developing and utilizing Islamic legal traditions in the conservation of biodiversity. Keywords: Conservation, Biodiversity, Islam